2020
DOI: 10.1177/2309499020937827
|View full text |Cite
|
Sign up to set email alerts
|

Posterior sloping angle of the capital femoral physis in slipped capital femoral epiphysis has poor clinical utility and should not guide treatment on prophylactic fixation

Abstract: Background: Prophylactic pinning of the uninvolved side after unilateral slipped capital femoral epiphysis (SCFE) is controversial as it balances increased surgical risks against the possibility of protecting a normal hip from initial slip and deformity. A posterior sloping angle (PSA) of greater than 12–14.5° has been proposed by various authors as a treatment threshold to predict for contralateral hip progression and prophylactic pinning. Methods: A retrospective review of a 10-year series of patients with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Our study suggests that PSA might be used as the additional quantitative parameter in decision-making in patients presenting with primary unilateral SCFE, but should not serve as the only guide to rely on. That matches the findings presented in a study by Ou Yang, who also observed slightly higher values of PSA in isolated unilateral slip (15.8 o ) vs. subsequent contralateral progression (17.9 o ) but did not prove significant differences between the groups [26,27].…”
Section: Discussionsupporting
confidence: 90%
“…Our study suggests that PSA might be used as the additional quantitative parameter in decision-making in patients presenting with primary unilateral SCFE, but should not serve as the only guide to rely on. That matches the findings presented in a study by Ou Yang, who also observed slightly higher values of PSA in isolated unilateral slip (15.8 o ) vs. subsequent contralateral progression (17.9 o ) but did not prove significant differences between the groups [26,27].…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly enough, the initial PSA in the contralateral hip was not significantly different between the four groups of patients assessed in this study. Similar findings were published by Ou Yang et al ., [25] who also did not find significant differences in PSA between the Isolated Unilateral Slip and Subsequent Contralateral Progression groups. In our study, more than 70% of patients eventually developed CAM-type FAI.…”
Section: Discussionmentioning
confidence: 90%